2022
DOI: 10.3390/molecules27030600
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Staling Aldehydes in Lager Beer under Maritime Transport and Storage Conditions

Abstract: Beer flavor stability is greatly influenced by external temperature, vibrations, and longer delivery times. The present study assessed the impact of transport and storage conditions on staling aldehyde evolution in lager beers across five sample groups (fresh, transport, and storage simulation, and their controls), which differed in their bottle opening system (either crown cap or ring pull cap). Maritime transport conditions (45 days of travel, vibrations of 1.7 Hz, and warm temperatures (21–30 °C)) were simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The evolution of nine staling aldehydes after maritime transport with storage simulation (45 days of travel at 21–30 °C and 1.7 Hz and 75 days at 19–29 °C after transport simulation) in bottled lager beer evaluated in our previous study [ 9 ] were compared with the results of three forced ageing periods (7, 21, and 28 days at 37 °C), to assess the prediction power of this methodology for this particular family of compounds during beer maritime exportation. A total of five beer batches were analysed (B1–B5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The evolution of nine staling aldehydes after maritime transport with storage simulation (45 days of travel at 21–30 °C and 1.7 Hz and 75 days at 19–29 °C after transport simulation) in bottled lager beer evaluated in our previous study [ 9 ] were compared with the results of three forced ageing periods (7, 21, and 28 days at 37 °C), to assess the prediction power of this methodology for this particular family of compounds during beer maritime exportation. A total of five beer batches were analysed (B1–B5).…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous study, the four Strecker aldehydes identified in bottled lager beers tend to increase, up to three times higher, when beers are exposed to maritime transport conditions [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations